Operationalizing successful strategic planning processes in a high performing community college - Garstecki, Marcus, author; Jennings, Louise, advisor; Quick, Don, advisor; Walters, Jack, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2019)
This study assessed the effectiveness of the strategic planning processes in a high performing community college. Lake Area Technical Institute (LATI) in Watertown, South Dakota was identified as a high performing institution based on earning the 2017 Aspen Prize for Community College Excellence. The study utilized a qualitative, single site, case study to provide insight into the elements that led to a successful strategic planning process. The data collection included interviews with twenty-three employees including faculty, staff, and administration. A document analysis of relevant planning documents was conducted, as well as an observation of the college's strategic planning session, and observation of the institution's strategic planning and Aspen Prize related artifacts. The results of this study provide strategic planners insight into how a high performing institution created and successfully implemented a strategic plan. Four a priori codes, or main themes, were developed prior to the study to guide my research. These four themes included: employee perceptions of strategic planning, employee participation in the strategic planning process, implementing the strategic plan, and linking budgets and resources to support the strategic plan. Within these themes, findings suggest that the following factors contributed to successful planning efforts at LATI. Theme One indicated that an inclusive planning process that values employee engagement and a positive culture throughout the institution generated extensive support for the planning process. Theme Two indicated support for a cross-represented group of employees and external stakeholders in the process and most importantly, valuing the input received from those participants. The results from Theme Three indicated several steps that led to successful implementation: conducting an annual planning process, assigning responsibility to the initiatives that comprise the plan, utilizing committees or teams implement the initiatives, communicating the details of the strategic plan to the campus community through multiple methods, and regularly assessing the plan. Theme Four discusses the ongoing resource allocation process that occurs throughout the fiscal year that supports the strategic plan. The research also explored the impact of winning the Aspen Prize for Community College Excellence on the institution and how the Aspen process impacted the strategic planning process.
Keywords: higher education; strategic planning; planning; community college